Theoretical Smart Design and Control for an Atruamatic Grasper - H. Alnema, Yazen; Abdulmalek Ahmed, Mohammed; Venn, Simon (International Journal of Engineering and Technology, 2018)
Accurate knowledge of the grasping force is essential when avoiding tissue trauma during grasping and manipulation in abdominal surgery. The aim of this paper is to present a theoretical design of laparoscopic grasper complete with control system. Mechanically the design comprises of a load cell and actuator added to the traditional grasper. The original grasper was also modified slightly for example, the standard type of teeth were replaced with waveform teeth to maximise grip yet reducing the chance of tissue trauma.Â  Control wise the grasper works by the load cell measuring the applied force which then controls the actuator via the control system. The applied force on the tissue either increases or decreases so that the demand force and the output force applied to the tissue are the same. To simulate the force the load cell would experience the Generalised Maxwell model was used to simulate the viscoelastic characteristics of a biological tissue.